Lab life, seasons and chromosome fusions affect non-cell-autonomously proliferation and neurogenesis, but not oligodendrogenesis, in mice and voles - Athanasia Rapti; Theodosia Androutsopoulou; Evangelia Andreopoulou; Maria Mellou; Georgios Leventakos; Maria Anesti; Konstantina Mastori; Myrto Chatzopoulou; Paraskevi Smyrli; Nikiforos Lakos; Kawthar Muse; Georgios P. Mitsainas; et al. (Scientific Reports)
Abstract Environmental and behavioral factors have been shown, in experimental settings, to affect neurogenesis in the mouse brain. We found that the density of proliferating neural stem/progenitor cells (NSPCs) and of neuroblasts was significantly lower in the Subependymal Zone stem cell niche of lab mice when compared with mice and pine voles captured in the wild, with seasonal variation observed only in voles. Moreover, levels of proliferation and neurogenesis were found to decrease in proportion to the decrease in the numbers of chromosomes (from the typical 2n = 40 down to 2n = 26) caused by Robertsonian fusions. In contrast, oligodendroglial progenitors and microglial cells were unaffected by wildlife, seasons and chromosomal fusions. When NSPCs were grown in cultures no differences were detected, suggesting that environmental and genetic effects are mediated by non-cell-autonomous mechanisms. These “real-world” data provide a platform for the identification of systemic factors and genetic loci that control postnatal brain neurogenesis.